A prática pedagógica do professor de Atendimento Educacional Especializado para o aluno com deficiência intelectual - Oliveira Neta, Adelaide de Sousa (2013)
The present research was conducted in three public schools in Fortaleza-CE during the academic year of 2012, aiming to analyze the pedagogical practice of the teacher who works on Educational Specialized Service, dealing with studentwho has intellectual disabilities in theMultifunctional Resource Classroom (MRC). The special features found in the teaching practices in these contexts was also analyzed to identify the physical and pedagogical organization of MRC and the relevance of the objectives and activities according to the issue found in this population. As theoretical referential, the study has made use of the psychogenetic andsocial-interactionistpresuppositions ofPiaget e Vygotsky, respectively, as well as the contributions that guide the structural and functional aspects of students with intellectual disabilities. To support studies on Specialized Education Service, it was made use of several researches in the area and also legal documents that govern this service. As methodological approach, we opted for a qualitative study and for the method of multiple case study. As procedure for data collection, it was made use of semi-structured interview, observation based on a scale developed with this purpose, and documental analysis of AEE’s plans, case studies and records of activities. Three teachers from Public Schools (P1, P2 and P3), who attended students with intellectual disabilities (A1, A2 and A3), participated of this study. The results were recorded on a scale of observation, and,in a second moment, it was defined in three dimensions (1. multifunctional resources classroom: space of the Specialized Educational Service;2. Functions , Conceptions and Actions of the AEE teacher X Policy of Special Education in the perspective of Inclusive Education; 3. The student with intellectual disabilities and thepedagogical intervention of the teacher working in theMultifunctional, Resource Classroom). Each of them contains categories constituted of the grouping of the sub-items of the observation scale. The results demonstrated that the teachers followed a script to formulate the plan of AEE and they defined in their plans the frequency of visits, materials and resources, duration of the activities and organization of students at MRC. It was also observed that the teachers elaborated the case study based on the guide of proposition for a case and recorded the performance of students in specific instruments for this purpose. However, these activities do not always attend the relevant particularities of the nature of the AEE perspective. It was identified some proposals to support the curriculum contents, and also others based on ludic situations. The latter, in most cases, did not contribute to the cognitive development of students with intellectual disabilities. These proposals were guided by a variety of games and activities, but without the explicit mediation of the teacher. We understand that the Multifunctional Resources Classrooms constitute supportive spaces for the development of students who have intellectual disabilities. However, we observed that there are still practical challenges regarding to the understanding of AEE for this population. Many of them due to the fragility of the educational training of the teacher to be a specialist in this subarea, the lack of technical support, and the absence of interaction with the teachers of regular classroom.